The mechanisms of teaching and evaluation of the quality of performance of the text documents classifier - Lytvynov, V.V.; Moyseenko, O.P. (Математичні машини і системи, 2014)
Описані механізми навчання та оцінки якості роботи класифікатора в розроблюваній системі автоматизованої обробки великих об'ємів текстової інформації. Класифікатор базується на вільній бібліотеці LibSVM та методі опорних векторів. Система виконує функції пошуку, класифікації, рубрикації та кластеризації текстових документів за запитами користувача. Описываются механизмы обучения и оценки качества работы классификатора в разрабатываемой системе автоматизированной обработки больших объемов текстовой информации. Классификатор базируется на свободной программной библиотеке LibSVM и методе опорных векторов. Система выполняет функции поиска, классификации, рубрикации и кластеризации текстовых документов по запросам пользователя. The mechanisms of teaching and evaluation of the performance of the classifier in the developing system of the automated processing of large volumes of textual information are described. The classifier is based on the free software library LibSVM and support vector machines. The system performs the functions of search, classification, categorization and clustering of text documents at the request of the user